Legal Awareness of Motor Vehicle Users in Muara Karang Raya: A Study of Socio Legal - Herman, Ronaldo Heinrich (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Sexual violen Motorbike riders on Jalan Muara Karang Raya have violated pedestrians' rights to the sidewalk. This study found that the criminal sanctions stipulated in Article 284 of Law Number 22 of 2009 do not provide a deterrent effect. As a result, motorcyclists view their actions as a habit rather than a violation of the law. To increase legal awareness, this study recommends increasing the fines and/or imprisonment. Confiscation of driver's licenses is a new type of sanction that could provide a deterrent effect on violators. This study will analyze laws and regulations, observations, and interviews with relevant parties.